(untitled) (Revista Educação, Artes e Inclusão, 2020)
This study analyzes an experience carried out in Brazil in which children diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) and relational problems, users of a Psychosocial Care Center for Children and Adolescents (CAPSi), participate in an atelier of literature reading. The proposal of “Oficina da Palavra” is to offer an alternative to the use of medicines as the central mode of treatment, through a collective and participative device of reading and care. The atelier was held as an intervention research based on the cartography method. It emphasizes the joint dimension of attention and the importance of building ecosystems in which attention to oneself and to others is cultivated. From an ecological perspective that goes beyond individualistic and naturalistic views of attention, care for attention problems emerges as a work of cultivating correspondence and joint, opened concentrated attention, involving the construction of favorable ecosystems.